Interaction Between Vitamin B12 Status and Lipid Profile Among Children and Adolescents with Type I Diabetes - Abdelghany, Ramy Saleh; Abdelhamid, Nehal; Salem Abu Elhassan, Mohamed Gamal; Abd El Dayem, Soha Mahmoud; Kamel, Mai Hamed (Journal of Neonatal Surgery, 2025)
Background: Vitamin B12(VIT B12), also known as Cobalamin, is a water-soluble vitamin that acts as a coenzyme. It plays pivotal role in keeping healthy neurons and the synthesis of RBCs, making it crucial during early growth stages. Humans fulfill their nutritional needs for vitamin B12 through combined gut microbial biosynthesis and food consumption. Aim and objectives: To evaluate the serum level of vitamin B12 in children and adolescents with type 1 diabetes. Methods: This cross-sectional study was conducted on 61 children and adolescents with type 1 diabetes patients were recruited from the endocrine clinic, Military hospitals, Cairo, Egypt and 21 healthy matched control group. Serum vitamin B12 and lipid profile were measured. Results: There were statistically significant higher levels in cases than control regarding total cholesterol, HDL and LDL, while there was statistically significant decrease regarding triglycerides. Vitamin B12 was statistically lower in patients group than control group. There was no statistically significant relation between VIT B12 and BMI. While, there was significant negative correlation between VIT B12, triglyceride and LDL at p=0.021 and 0.043 respectively. Conclusions: Our study underscores the necessity of comprehensive clinical and monitoring in type 1 diabetic patients. The correlation of vitamin B12 with lipid biomarkers is particularly relevant for managing cardiovascular risk in this population.